Is There Evidence for Biologically Significant Size-Selective Mortality of Coho Salmon During the First Winter of Marine Residence?. Issue 3 (4th May 2017) - Beacham, Terry D.; Neville, Chrys M.; Tucker, Strahan; Trudel, Marc
Abstract: We examined whether individual Coho Salmon Oncorhynchus kisutch in southern British Columbia had to achieve a sufficient size ("critical size") by the end of the first marine summer to be able to survive through the ensuing fall and winter. Descriptive statistics of seasonal weight distributions were determined. The expected body weight of an individual sampled in one season was projected to the next season with a growth equation tested on Pink Salmon O. gorbuscha . Projected weight frequencies were then compared with observed weight frequencies in the next season to evaluate whether it was necessary to invoke size-selective mortality to explain the observed weight frequencies in the next season. Based on estimated growth between July and September, a maximum of 9% of the stock in the Strait of Georgia may have been subjected to size-selective mortality—far lower than the 63–74% mortality estimated in previous studies. Likewise, there was basically no size-selective mortality between September and November, yet 48% mortality had been reported previously for this period. We could find no evidence of any critical size that age-1.0 Coho Salmon juveniles in southern British Columbia had to attain by the end of the first summer or fall of marine rearing to enable them to survive the subsequent winter in the ocean. Thus, there was no support for the hypothesis that Coho Salmon had to achieve a sufficient (critical) size by the end of the first marine summer or fall to be able to survive during the winter of their first year of ocean rearing. Received May 31, 2016; accepted January 18, 2017 Published online March 15, 2017